(untitled) (Journal of Pharma Insights and Research, 2025)
Ruta graveolens, commonly known as rue, has been utilized in traditional medicine systems for treating parasitic infections. The present study aimed to evaluate the anthelmintic potential of R. graveolens aqueous extract against gastrointestinal nematodes using Lumbricus terrestris as a model organism. The plant material was authenticated, processed, and extracted using water as a solvent through refluxation. Phytochemical screening showed the presence of various bioactive compounds including alkaloids, flavonoids, glycosides, tannins, and carbohydrates. The anthelmintic activity was assessed by monitoring paralysis and death times of earthworms exposed to different concentrations of the extract. At 25 mg/mL concentration, the aqueous extract demonstrated superior anthelmintic activity compared to the standard drug albendazole (10 mg/mL), with paralysis time of 90 seconds and death time of 190 seconds. In contrast, albendazole showed paralysis at 300 seconds and death at 1500 seconds. The extract’s enhanced anthelmintic activity may be attributed to the presence of bioactive compounds including alkaloids, flavonoids, and phenolic substances. The findings signify the traditional use of R. graveolens in parasitic infections and suggest its potential as a natural anthelmintic agent. The study provides a scientific basis for further investigation into the isolation and characterization of active compounds responsible for the observed anthelmintic activity